Kesejahteraan Pengerajin Pandai Besi Tradisional di Kopang Lombok Tengah - Hulaimi, Ahmad; Anggraini, Lisa (Universitas Muhammadiyah Mataram, 2023)
Abstract: This research is motivated by developments in the modern era which have resulted in many new business actors emerging. This is a challenge for traditional blacksmith industry players in Montong Gamang Village, Kopang District, Central Lombok to continue trying to win the existing competition in order to maintain the continuity of the industry that has been running for a long time. So, blacksmith industry players who still use traditional technology are required to determine development strategies for the welfare of the community of blacksmith craftsmen in Montong Gamang Village appropriately so that their businesses are able to compete and develop amidst the times. This research aims to determine the development strategies implemented by craftsmen at the traditional blacksmith industry center in Montong Gamang Village in facing business competition. To find out the supporting and inhibiting factors faced by craftsmen in developing a traditional blacksmith industrial center in Montong Gamang Village to face business competition. This type of research is qualitative which uses a descriptive approach. The methods used in collecting data are interviews, observation and documentation. Data analysis techniques are carried out through collecting information and reducing data from the local community.Abstrak: Penelitian ini dilatar belakangi oleh perkembangan zaman yang serba modern membuat banyaknya pelaku usaha baru bermunculan. Hal ini merupakan tantangan bagi para pelaku industry pengerajin pandai bes itradisional di Dusun Mumbang Kecamatan KopangLombok Tengah untuk terus berupaya memenangkan persaingan yang ada guna mempertahankan kelangsungan industri yang sudah lama dijalankan. Sehingga para pelaku industri pandai besi yang masih menggunakan teknologi tradisional dituntut untuk menentukan strategi pengembangan demi kesejahteraan masyarakat pengerajin pandai besi di Dusun Mumbang dengan tepat agar usahanya mampubersaing dan berkembang ditengah perkembangan zaman. Penelitian ini bertujuan untuk mengetahui strategi pengembangan yang diterapkan oleh para pengrajin sentra industri pandai besi tradisional di Desa Montong Gamang dalam menghadapi persaingan usaha. Mengetahui faktor pendukung dan penghambat yang dihadapi para pengrajin dalam melakukan pengembangan sentra industri pandai besi tradisional di Desa Montong Gamang untuk menghadapi persaingan usaha. Jenis penelitian ini adalah kualitatif yang menggunakan pendekatan deskriptif. Metode yang digunakan dalam pengumpulan data yaitu wawancara, observasi dan dokumentasi. Teknik analisis data dilakukan melalui pengumpulan informasi, reduksidata dari masyarakat setempat.